Circulating Aspergillus fumigatus DNA Is Quantitatively Correlated to Galactomannan in Serum - Alanio, Alexandre; Menotti, Jean; Gits-Muselli, Maud; Hamane, Samia; Denis, Blandine; Rafoux, Emmanuel; Peffault de la Tour, Régis; Touratier, Sophie; Bergeron, Anne; Guigue, Nicolas; Bretagne, Stéphane (Frontiers in Microbiology, 2017)
The performance of antigen galactomannan (GM) for diagnosing invasive aspergillosis (IA) is hampered by the occurrence of false-positive results. Quantitative PCR has been proposed to improve the diagnosis of IA. Therefore, we analyzed the value of performing a PCR test to the GM-positive serum sample. Using a quantitative PCR assay specific for Aspergillus fumigatus 28S ribosomal DNA, we retrospectively tested 422 GM-positive (Platelia Bio-Rad kit) serum samples collected over 1 year from 147 patients. The cases were classified based on EORTC criteria as “proven,” “probable,” and “no–IA” before availability of the PCR results. After exclusion of 65 samples for non-reproducibility of GM positivity (n = 62) or PCR inhibition (n = 3), 75 (21.0%) of the remaining 357 samples were PCR-positive. GM and fungal DNA showed a significantly positive correlation (p < 0.0001, R2 = 0.27, slope = 0.98 ± 0.19). At least one PCR-positive result was observed in 63.3% (31/49) of IA patients and in 13.2% (13/98) of non-IA patients (p < 0.0001). The PCR positivity was also associated with the presence of other microbiological criteria among the 44 patients with IA and complete mycological workup (p = 0.014), as well as a higher mortality rate at six months among the 135 patients with hematological conditions (p = 0.0198). Overall, we found a quantitative correlation between serum GM and circulating DNA with an increased likelihood of IA when both were positive. A PCR-positive result also supported a higher fungal load when GM was already positive. We advocate adding a PCR test for every confirmed GM-positive serum sample.